Lost in Transition: A Two-Year Collaborative Autoethnography of South Korean Doctoral Students’ Development and Identity Negotiation - Kim, Miso; Cho, Eunhae (Journal of International Students, 2022)
This collaborative autoethnography (CAE) explores the lived experiences of two South Korean doctoral students’ transnational career transitions during 2019–2021. The purpose of the CAE is twofold: (a) to analyze international doctoral students’ development during the transition; and (b) to investigate negotiations of their intersectional identities. The data came from our biweekly multimodal narratives on our development (96 total) and biweekly meeting transcripts (48 total). We thematically analyzed (Braun & Clarke, 2006) the data first, found two themes, and reconstructed our two-ear narratives and visually represented them. The data analysis revealed that our major challenges during transition were to receive developmentally appropriate help (responsive mediation; Johnson & Golombek, 2016) and to build transnational, intersectional identities in a liminal space (Bhabha, 1994) between different geographical locations. Based on our two-year dialogue data, we offer suggestions for negotiating appropriate levels of mediation and reframing intersectional and liminal identities in a liberating way.